2014
DOI: 10.3390/v6020524
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Antibodies against Hantaviruses in Serum and Saliva of Adults Living or Working on Farms in Yorkshire, United Kingdom

Abstract: Hantaviruses are an established cause of haemorrhagic fever with renal syndrome (HFRS) in Europe. Following a confirmed case of HFRS in the UK, in an individual residing on a farm in North Yorkshire and the Humber, a tidal estuary on the east coast of Northern England, and the subsequent isolation of a Seoul hantavirus from rats trapped on the patient’s farm, it was considered appropriate to further investigate the public health risk of this virus in the region. Of a total 119 individuals tested, nine (7.6%) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
19
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 17 publications
3
19
0
1
Order By: Relevance
“…While acknowledging the concerns of Clements et al , we stand by the key findings and design of our study, which has provided new data on the seroprevalence of hantavirus infection in a farming community in which the first molecularly confirmed case in the UK had recently been detected [2]. More detailed studies logically follow on from these preliminary findings and are now in progress.…”
supporting
confidence: 51%
See 1 more Smart Citation
“…While acknowledging the concerns of Clements et al , we stand by the key findings and design of our study, which has provided new data on the seroprevalence of hantavirus infection in a farming community in which the first molecularly confirmed case in the UK had recently been detected [2]. More detailed studies logically follow on from these preliminary findings and are now in progress.…”
supporting
confidence: 51%
“…We acknowledge Clement and colleagues for their comments [1] on our paper [2]. We agree that many controversies are being discussed by the hantavirus community, particularly surrounding the interpretation of serological results and the designation of new species and strains.…”
mentioning
confidence: 94%
“…In Europe, a few severe clinical human cases of SEOV infections have been confirmed in the UK and France, where the source of infection was established as pet rats [18,19]. Furthermore, a serosurvey among farmers exposed to wild rats showed a seroprevalence of 8% in the UK [20]. Since 2000, the presence of SEOV in wild brown rats was demonstrated in Belgium, France and the UK [18,2123].…”
Section: Introductionmentioning
confidence: 99%
“…There is serological evidence of human infection with PUUV-or SNV-like viruses in the UK [29], though there has been no molecular evidence of these viruses in either humans or rodents. A previous study has reported that blood from a vole infected with TATV B41 is cross-reactive with PUUV, which suggests that PUUV/SNV seropositive humans may have been the result of TATV infection [20].…”
Section: Discussionmentioning
confidence: 99%